Youth, work, and equity: rethinking decent work through gender lens - Andrade, Cláudia; Neves, Paula C.; Bessa, Inês (Frontiers in Sociology, 2025)
IntroductionDecent work and gender equality are critical for fostering sustainable economic and social development. Even though the last three decades have seen several positive advancements in gender equality, disparities still exist in several ways, with research indicating that young women face more obstacles to employment and professional advancement than their male counterparts.MethodsAn on-line cross-sectional survey was conducted with a sample of 190 Portuguese young adults who work to examine key factors of decent work such fundamental principles and values at work, adequate working time and workload, fulfilling and productive work, meaningful remuneration for the exercise of citizenship, social protection, opportunities and health and safety.ResultsThe analysis reveals gender differences in most of the dimensions of decent work, suggesting that gender plays a significant role in shaping these perceptions. Findings also suggested differential effects of having a team leader position and work schedules for male and female young workers.DiscussionUnderstanding these gendered perceptions is crucial for policymakers and employers aiming to promote gender equality and decent work for all. By addressing the specific perceptions of decent work both men and women using the gender equity lens can raise awareness about the barriers that act against equitable work environments, enabling to both men and women to create a positive future for themselves, their families, and their communities.